2022
DOI: 10.56911/jik.v1i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Building Integrated Photovoltaic Application for Apartment Building in Jakarta

Abstract: In sustainable development concept, energy efficiency and conservation measurements are paramount to reduce the level of building energy consumption. Utilization of such device diminishes the building dependency to the grid which is still dominated by energy from fossil fuels. Implementation of BIPV (Building Integrated Photovoltaic) system is expected to be one of the best possible choices for a tropical country such as Indonesia with abundance of solar radiation. With the existence of BIPV system, it is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…One of those things, BIM is a powerful tool that simulates a real model of a building to determine its characteristics and the actual solar insolation values it has (Al Janahi, 2020). Then, the implementation of Building an Integrated Photovoltaic (BIPV) system is expected to be one of the best options for tropical countries like Indonesia, with abundant solar radiation (Harani, 2022). In another research by (Husin et al, 2021) about the implementation of solar PV on the walls of the Hotel building, it can be concluded that the decrease obtained is 47.32% of electricity.…”
Section: Literature Studymentioning
confidence: 99%
“…One of those things, BIM is a powerful tool that simulates a real model of a building to determine its characteristics and the actual solar insolation values it has (Al Janahi, 2020). Then, the implementation of Building an Integrated Photovoltaic (BIPV) system is expected to be one of the best options for tropical countries like Indonesia, with abundant solar radiation (Harani, 2022). In another research by (Husin et al, 2021) about the implementation of solar PV on the walls of the Hotel building, it can be concluded that the decrease obtained is 47.32% of electricity.…”
Section: Literature Studymentioning
confidence: 99%
“…The energy efficiency of buildings is one of the most important characteristics to be assessed to achieve sustainability in the built environment [23]. Then, the implementation of building an integrated photovoltaic system is expected to be one of the best options for tropical countries like Indonesia, which have abundant solar radiation [24]. In another study by [25] about the implementation of solar PV on the walls of the hotel building, it can be concluded that the decrease obtained is 47.32% of electricity.…”
Section: Renewable Energy and Bimmentioning
confidence: 99%